2002
DOI: 10.1063/1.1483118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonuniformity in thin-film photovoltaics

Abstract: We discuss the physical origin and effects of micrononuniformities on thin-film photovoltaics. The key factors are the large device area and the presence of potential barriers in the grain boundaries (for polycrystalline films) and in device junctions. We model the nonuniformity effects in the terms of random microdiodes connected in parallel through a resistive electrode. The microdiodes of low open circuit voltages are shown to affect macroscopically large regions. They strongly reduce the device performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 8 publications
1
64
0
Order By: Relevance
“…8,9,13,18,19 Some equivalent circuits incorporating a parasitic weak diode have also been proposed to account for these nonlinear shunts. [19][20][21] However, these macroscopic, circuit level models cannot account for the microscopic nature of shunt paths. The physical origin of shunt conduction paths have also been explored in the literature.…”
Section: ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,13,18,19 Some equivalent circuits incorporating a parasitic weak diode have also been proposed to account for these nonlinear shunts. [19][20][21] However, these macroscopic, circuit level models cannot account for the microscopic nature of shunt paths. The physical origin of shunt conduction paths have also been explored in the literature.…”
Section: ͑1͒mentioning
confidence: 99%
“…The analysis of shunt leakage phenomena is hampered, in part, because most models of the dark current typically focus on the forward bias current at one temperature only. 12,14,20,25 A detailed characterization of the shunt current, considering the entire voltage range at different temperatures, is usually not performed. Moreover, the picture of shunt leakage has been fragmented because the nature of shunt current has been assumed to be unique for solar cell technologies.…”
Section: ͑1͒mentioning
confidence: 99%
“…Many studies have identified various efficiency loss mechanisms, 7,8 one of which is the nonuniformity of the crystals in polycrystalline films. 2,[9][10][11][12] In this paper, the phrase ''random polycrystalline'' refers to the situation in which the morphology and crystal quality of the grains are uncorrelated or only slightly correlated. The term ''nonuniformity'' describes a wide variation in the morphology and crystal quality of the grains.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of back contact and processes on cell durability have been discussed for example in [3][4][5]. More recently, the detrimental effects of localized shunts [6], the general effects of film micrononuniformities [7], and the effect of cell-fabrication processing through formal design-of-experiments methodologies [8] have been reported.…”
Section: Introductionmentioning
confidence: 99%